Analisis Pengaruh Kualitas Produk, Citra Merek, Harga Dan Promosi Terhadap Keputusan Pembelian Hijab Rabbani - Kurniawati, Erna (Diponegoro Journal of Islamic Economics and Business, 2023)
Currently, the development of Muslim fashion is very fast. This makes Muslim fashion manufacturers experience tough competition. The efforts made to win market competition are always following the times, fulfilling needs, having creativity and innovation and being able to identify factors that are considered by consumers. This study aims to analyze the effect of the independent variables, namely product quality, brand image, price and promotion on the purchase decision of the Rabbani hijab as the dependent variable. The population in this study were Students of the Islamic Economics Study Program, Diponegoro University Class of 2019-2022 who had bought and used the Rabbani hijab. A sample of 100 respondents with a purposive sampling approach. The data collection method is through a questionnaire with multiple linear regression analysis techniques. The results show that partially the product quality variable has no effect on the purchase decision of the Rabbani hijab. Meanwhile, brand image, price and promotion variables influence the purchasing decision of Rabbani hijab. Simultaneously all variables have a positive and significant effect on the purchase decision of the Rabbani hijab.